1993
DOI: 10.1037/0003-066x.48.7.839
|View full text |Cite
|
Sign up to set email alerts
|

The public's knowledge about psychologists and other mental health professionals.

Abstract: A random sample of New London County, CT, residents received a questionnaire about nine mental health professions or professionals (MHPs): clergyperson, marriage and family counselor, nonpsychiatric physician, psychiatrist, psychiatric nurse, psychologist, psychotherapist, social worker, and telephone crisis counselor. Respondents defined each MHP and reported their satisfaction with treatment, which MHP they would recommend, their referral source(s), licensure requirements, and fees. A mixed-design analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 13 publications
6
30
0
Order By: Relevance
“…Only 6% of respondents correctly identified that the APS‐recommended fee for a 45‐ to 60‐min consultation was $206, whereas 69% and 78% failed to acknowledge the centrality of the therapeutic relationship and discussions on thoughts and feelings, respectively, during a typical consultation with a counselling psychologist. Taken together, these findings are consistent with previous research that has shown that the general public “has some knowledge but lacks one or more essential facts” (Murstein & Fontaine, 1993; pp. 840–84).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only 6% of respondents correctly identified that the APS‐recommended fee for a 45‐ to 60‐min consultation was $206, whereas 69% and 78% failed to acknowledge the centrality of the therapeutic relationship and discussions on thoughts and feelings, respectively, during a typical consultation with a counselling psychologist. Taken together, these findings are consistent with previous research that has shown that the general public “has some knowledge but lacks one or more essential facts” (Murstein & Fontaine, 1993; pp. 840–84).…”
Section: Discussionsupporting
confidence: 92%
“…The consistent finding that clients or individuals with a previous client history with a psychologist exhibit greater knowledge of the profession (Hopson & Cunningham, 1995; Murstein & Fontaine, 1993) was supported by the results of the present study. Responses to the open‐ended question concerning perceived differences between counselling and clinical psychologists supported previous research that revealed that while overlap exists (Osipow, Cohen, Jenkins, & Dostal, 1979; Watkins, Schneider, Hap Cox, & Reinberg, 1987), the primary distinction made between the professions concerned relative activities associated with the normality–pathology continuum (Tipton, 1983).…”
Section: Discussionsupporting
confidence: 86%
“…This result was probably because of the fear of stigma or labeling associated with psychological treatment (see Stones, 1996;Murstein & Fontaine, 1993;Furnham & Wardley, 1990).…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies considered only attitudes towards psychological services (e.g., Stones, 1996;von Sydow & Reimer, 1998), knowledge about the psychosocial professions (Murstein & Fontaine, 1993) or perceptions of mental health services (Bram, 1997;Fall, Levitov, Jennings & Eberts, 2000;Warner & Bradley, 1991). Most of the research involved quantitative empirical studies.…”
Section: The South African Contextmentioning
confidence: 99%
“…When psychiatric assistances are needed, the majority would turn to their primary care physicians for mental health consultation and services (Mickus, Colenda, & Hogan, 2000;Murstein & Fontaine, 1993). Among others, Keen (1998) has expressed concerns that the treatment of psychological issues with pharmacotherapy have been driven not by expertise but by professional convenience, popular demands, insurance protocols, and so forth.…”
mentioning
confidence: 98%